Factors Associated with Hepatitis B Surface Antigen Kinetics and Responses in Pegylated Interferon Alpha-2a Monotherapy for Patients with Chronic Hepatitis B - Itokawa, Norio (Intern Med, 2021)
OBJECTIVE: Pegylated-interferon monotherapy is the standard treatment for patients with chronic hepatitis B; however, the factors associated with its therapeutic effects remain unclear. METHODS: Patients with chronic hepatitis B were treated with pegylated interferon α-2a for 48 weeks. We evaluated the kinetics of hepatitis B surface antigen (HBsAg) during treatment and follow-up periods and the factors associated with an HBsAg response (defined as a change in HBsAg of ≥-1 log IU/mL from baseline). RESULTS: The study population comprised 50 patients. The median baseline levels of hepatitis B virus DNA and HBsAg were 5.00 and 3.40 log IU/mL. The median values of HBsAg reduction from baseline were -0.44 (n=48), -0.41 (n=40), and -0.68 (n=11) log IU/mL at the end of treatment and at 48 and 144 weeks post-treatment, respectively. The rates of HBsAg response were 24.0% and 22.5% at the end of treatment and at 48 weeks post-treatment, respectively. A multivariate analysis identified HBsAg <3.00 log IU/mL as an independent baseline factor contributing to the HBsAg response at the end of treatment and 48 weeks post-treatment (p=1.07×10(-2) and 4.42×10(-2), respectively). There were significant differences in the reduction of the HBsAg levels at 12 weeks of treatment and in the incidence of serum ALT increase during treatment between patients with and without an HBsAg response. CONCLUSION: These findings suggest that the baseline HBsAg level, HBsAg kinetics at 12 weeks of treatment, and ALT increase during treatment are important factors contributing to the HBsAg response in pegylated interferon α-2a monotherapy for patients with chronic hepatitis B.